Predictive and concurrent validity of pain sensitivity phenotype, neuropeptidomics and neuroepigenetics in the MI-RAT osteoarthritic surgical model in rats - Otis, Colombe; Cristofanilli, Katrine-Ann; Frezier, Marilyn; Delsart, Aliénor; Martel-Pelletier, Johanne; Pelletier, Jean-Pierre; Beaudry, Francis; Lussier, Bertrand; Boyer, Alexandre; Troncy, Eric (Frontiers in Cell and Developmental Biology, 2024)
Background: Micro-RNAs could provide great insights about the neuropathological mechanisms associated with osteoarthritis (OA) pain processing. Using the validated Montreal Induction of Rat Arthritis Testing (MI-RAT) model, this study aimed to characterize neuroepigenetic markers susceptible to correlate with innovative pain functional phenotype and targeted neuropeptide alterations.Methods: Functional biomechanical, somatosensory sensitization (peripheral -via tactile paw withdrawal threshold; central -via response to mechanical temporal summation), and diffuse noxious inhibitory control (via conditioned pain modulation) alterations were assessed sequentially in OA (n = 12) and Naïve (n = 12) rats. Joint structural, targeted spinal neuropeptides and differential expression of spinal cord micro-RNAs analyses were conducted at the sacrifice (day (D) 56). The MI-RAT model caused important structural damages (reaching 35.77% of cartilage surface) compared to the Naïve group (P < 0.001). This was concomitantly associated with nociceptive sensitization: ipsilateral weight shift to the contralateral hind limb (asymmetry index) from -55.61 ± 8.50% (D7) to -26.29 ± 8.50% (D35) (P < 0.0001); mechanical pain hypersensitivity was present as soon as D7 and persisting until D56 (P < 0.008); central sensitization was evident at D21 (P = 0.038); pain endogenous inhibitory control was distinguished with higher conditioned pain modulation rate (P < 0.05) at D7, D21 and D35 as a reflect of filtrated pain perception. Somatosensory profile alterations of OA rats were translated in a persistent elevation of pro-nociceptive neuropeptides substance P and bradykinin, along with an increased expression of spinal miR-181b (P = 0.029) at D56.The MI-RAT OA model is associated, not only with structural lesions and static weightbearing alterations, but also with a somatosensory profile that encompasses pain centralized sensitization, associated to active endogenous inhibitory / facilitatory controls, and corresponding neuropeptidomic and neuroepigenetic alterations. This preliminary neuroepigenetic research confirms the crucial role of pain endogenous inhibitory control in the development of OA chronic pain (not only hypersensitivity) and validates the MI-RAT model for its study.